Determinants of traditional Korean medicine utilization by individuals with physical disabilities: inference of causal relationships using Korea health panel data - Chihyoung Son; Jong-hyun Kim; Eunkyung Yoon; Eunji Ahn; Minjung Park; Dongsu Kim (BMC Complementary Medicine and Therapies)
Abstract Background The demand for health management services has grown among individuals with physical disabilities. It is noteworthy that a significant proportion of this demographic has sought the services of traditional Korean medicine (TKM). Nevertheless, there is a lack of research on the characteristics of TKM utilization within this population. Therefore, this study aims to explore the characteristics of individuals with physical disabilities who utilize TKM services, to support future policy development in TKM for enhancing the health and quality of life for individuals with physical disabilities. Methods The study utilized a dataset from the Korea Health Panel (KHP) version 1.7, from the years 2008 to 2018. A panel analysis was conducted to analyze the correlation between the characteristics of participants and their influence of the TKM utilization. Results Based on the panel logistic regression analysis, the probability of TKM utilization was higher for individuals with physical disabilities who were female (p < 0.001), had a chronic musculoskeletal disorder (p < 0.001), Charlson Comorbidity Index of 1 (p = 0.025), and multiple chronic conditions (p = 0.025). Based on the panel hybrid regression analysis, those covered with Medical Aid spent less on TKM than those covered with National Health Insurance (p < 0.001), while those who were female (p < 0.001), had chronic musculoskeletal disorders (p = 0.007), or multiple chronic conditions (p = 0.007) had higher medical expenses for TKM utilization. Conclusions Individuals with physical disabilities accompanying nonfatal chronic musculoskeletal disorders or other chronic conditions frequently utilized TKM services. Those covered by Medical Aid spent less on TKM, while females and individuals with chronic musculoskeletal disorders or multiple chronic conditions incurred higher medical expenses for TKM. These results suggest the need for targeted interventions and policy changes to improve TKM access and address financial burdens for people with disabilities.